Konseling Gaya Belajar Peserta Didik Berdasarkan Teori VARK dan Implementasinya Dalam Pembelajaran Berdiferensiasi: Student Learning Style Counseling Based on VARK Theory and Its Implementation in Differentiated Learning - Mochammad Ronaldy Aji Saputra; Suryadi (UIN Kiai Haji Achmad Siddiq Jember, 2023)
This research aims to examine the role of student learning style counseling based on Visual, Auditory, Reading/Writing and Kinesthetic (VARK) Theory in the context of differentiated learning. Students' learning styles are an important factor that influences their ability to understand and remember information. Therefore, a deep understanding of individual learning styles is key to developing an effective learning approach. This research uses a literature study method, where researchers investigate the relationship between VARK Theory and differentiated learning, and investigate how the learning styles of counseling students can increase the effectiveness of differentiated learning through library sources. The literature sources that have been researched are then analyzed using the content analysis method. The results of this research indicate that student learning style counseling based on VARK Theory can make a significant contribution in increasing students' understanding of the best way to learn. With proper guidance, students can identify their learning style preferences and use them to optimize their learning experience. In addition, the integration of this concept in differentiated learning can help teachers teach more effectively by considering individual differences in students' learning styles. This research provides valuable insight for educational counselors, teachers and educational policy makers to understand the importance of counseling students' learning styles based on VARK Theory in the context of differentiated learning.